Konflik Batin dalam Novel Raumanen Karya Marianne Katoppo - Ismi Nur Afni; Zulfadhli Zulfadhli (Persona: Kajian Bahasa dan Sastra, 2022)
This study aims to describe: (1) the form of inner conflict in Marianne Katoppo's Raumanen, (2) the factors causing inner conflict in Marianne Katoppo's Raumanen, and (3) the impact of inner conflict in Marianne Katoppo's Raumanen. The object of this research is the novel Raumanen by Marianne Katoppo, published in 2018. This research is a type of literary research, which uses descriptive research methods. The data in this study are the sentences or explanations of the narrator, the speech of the characters, or the actions of the characters contained in the novel Raumanen by Marianne Katoppo. The instrument in this study was the author himself with the help of another instrument in the form of a recording sheet. The data collection techniques in this study were reading and understanding the whole novel, marking the utterances of the characters and the narrator, and taking an inventory of the data. The data validation technique in this research is by using triangulation technique. Data analysis techniques in this study include grouping, analyzing, interpreting, and drawing conclusions. The results of the study stated (1) the form of inner conflict in Marianne Katoppo's novel Raumanen in the form of approaching-close conflict, approaching-away conflict, and far-away conflict, (2) the factors causing inner conflict in Marianne Katoppo's Raumanen, namely, aggression theory, theory loss, personality theory, cognitive theory, helplessness theory, and behavioral theory, (3) the impact of inner conflict in Marianne Katoppo's novel Raumanen, namely frustration, helplessness, and anger.